Current status of and strategies for hepatitis C control in South Korea - Kim, Beom Kyung (Clin Mol Hepatol, 2017)
Chronic hepatitis C (CHC) is caused by hepatitis C virus (HCV) infection. HCV infection causes acute hepatitis, and the majority of those infected progress to chronic hepatitis, and some of them develop cirrhosis and hepatocellular carcinoma. Transmission of HCV is parenteral, and the major transmission routes include drug abuse, insecure injections or medical procedures, contaminated syringes or needles, sexual contact with an HCV-infected person, vertical infection of newborns by infected mothers, the transfusion of blood or blood products contaminated with viruses, and organ transplants. As no vaccine against HCV is available, HCV management involves blocking routes of transmission transmission, screening for HCV infection, and protecting liver disease progression by treatment. Highly potent oral direct antiviral agents are now available. Therefore, early detection through nation-wide screening program and appropriate treatment should be implemented to improve the quality of life of patients with HCV. Furthermore, for the effective HCV control in South Korea, The organization of an ‘integrated national viral hepatitis control system’ is desirable.